1995
DOI: 10.1093/jmedent/32.5.605
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Activity Patterns of Lutzomyia longipalpis (Diptera: Psychodidae) at an Endemic Focus of Visceral Leishmaniasis in Colombia

Abstract: Nocturnal activity of the sand fly Lutzomyia longipalpis (Lutz & Neiva) was studied from August 1991 to July 1992 in a small rural community in Colombia where American visceral leishmaniasis is endemic. During 2 or 3 nights each month, sand flies were collected with hand-held aspirators each hour between 1730 and 0630 hours, from a pigpen and a cattle corral located 30 m apart. Host-seeking activity of L. longipalpis adults was characterized by 2 general patterns: (1) adult sand fly activity increased shortly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0
5

Year Published

1997
1997
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 0 publications
3
37
0
5
Order By: Relevance
“…Morrison et al (1995) reported that during the 10 months of their survey in an endemic region of visceral leishmaniasis in Colombia, male Lutzomyia longipalpis (Lutz and Neiva, 1912) composed 60% and 83% of the collections conducted at the pigpen and at the cattle corral, respectively. Similar results were obtained by Reza and Mansour (2006) who collected significantly more males than females of both P. papatasi (85%) and P. sergenti (70%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morrison et al (1995) reported that during the 10 months of their survey in an endemic region of visceral leishmaniasis in Colombia, male Lutzomyia longipalpis (Lutz and Neiva, 1912) composed 60% and 83% of the collections conducted at the pigpen and at the cattle corral, respectively. Similar results were obtained by Reza and Mansour (2006) who collected significantly more males than females of both P. papatasi (85%) and P. sergenti (70%).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that male sand flies arrive on their host first, form an aggregation and wait for the females for mating. This "lekking" behaviour of the males is believed to allow them to disperse high levels of sex pheromone to attract females and increase their chances to mate (Morrison et al 1995;Killick-Kendrick 1999). During the summer season, the villagers in our study area sleep outside of their houses and keep their animals in open shelters where we set our traps.…”
Section: Discussionmentioning
confidence: 99%
“…However, in Colombia, two patterns of nocturnal activity of Lu. longipalpis were reported, one peaked early in the evening (18.30-23.30 hours) and then declined towards the morning, with an increased activity also above 24 ºC 25 . In Venezuela the greatest activity of this species was recorded before 23.00h 15 , and in Maranhão, Brazil, in animal sheds Lu.…”
Section: Discussionmentioning
confidence: 97%
“…It is also clear from both laboratory and field work that female sandflies are able to discriminate between a wide range of different types of hosts that may be available and females tend to feed on one host selected from many possible (Morrison et al, 1995). Although this is partly because of the interaction of host odour components and the male sex pheromone (see below) it is likely also that choice is based on odour components present.…”
Section: Host Odour Kairomonesmentioning
confidence: 99%